Incorporating time lags and uncertainty in cost-benefit analysis of water quality improvements – a case study of Limfjorden, Denmark - Tobias Holmsgaard Larsen; Thomas Lundhede; Søren Bøye Olsen; Brian H. Jacobsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2021)
Cost-benefit analyses are commonly applied to assess the net welfare effects of policies to improve surface water quality. These analyses often disregard the biophysical fact that from implementation of policy measures to resulting improvements on water quality there will typically be considerable time lags, and in many cases there is a risk that the measures will not actually lead to the expected improvement. Based on a case study, we show that explicitly accounting for such time lags and outcome uncertainty in the benefit estimation can have non-negligible impacts on cost-benefit analysis findings. Our analysis indicates that reaching the EU Water Framework Directive target for our case study will lead to large and robust welfare increases. Even if the target proves more difficult or more costly to reach than expected with known policy measures, our results suggest that attempting to do so will still lead to a net welfare gain to society. Increasing time lags and uncertainty regarding water quality improvements do decrease the benefits, but the benefits still outweigh the aggregate costs of policy measures. Only in the worst case scenario, combining a long time lag and a high level of outcome uncertainty for the water quality improvement with relatively high costs of policy measures, we are close to a break-even. Hence, we do not find evidence supporting a case for disproportional cost exemption from the WFD target being relevant for the Limfjorden case.
Keywords: D61; Q25; Q51; Q53; Q58; 330; Cost-benefit analysis; disproportional costs; time lags; uncertainty; water quality